THE FACTORS RELATED TO THE INCIDENCE OF HYPEREMISSIES OF GRAVIDARUM IN TRIMESTER PREGNANT MOTHERS IN SUDIANG RAYA HEALTH CENTER MAKASSAR - Yuliani Siradjudin (Stikes Graha Edukasi Makassar, 2019)
Introduction: The purpose of this study is to determine actors related to incidence of hyperemesis gravidarum in trimester I of pregnant women. Method: The research design is quantitative using observational and cross sectional study. The research population comprises all tpregnant women registered in the medical records and received pregnancy examination in Sudiang Raya Health Center, Makassar from March through April 2017. From the total population of 124 pregnant women, 94 were chosen as samples using quota sampling technique. Results: The research results indicated that there is a correlation between gravidity and the incidence of hyperemesis gravidarum ( p = 0.000), The research result reveals that there is a correlation between age and the incidence of hyperemesis gravidarum ( p = 0.000). The research result also reveals that there is a correlation between parity and the incidence of hyperemesis gravidarum (p=0.000) The research result also reveals that there is a correlation between anemia and the incidence of hyperemesis gravidarum ( p = 0.000). Conclusion: The conclusion of the research is that there is a significant correlation between gravidity, age, parity, and anemia and the incidence of hyperemesis gravidarum.